The State of Art of Extracellular Traps in Protozoan Infections (Review) - Zhang, Jing; Sun, Ying; Zheng, Jingtong (Frontiers in Immunology, 2021)
Protozoan parasite infection causes severe diseases in humans and animals, leading to tremendous economic and medical pressure. Natural immunity is the first line of defence against parasitic infection. Currently, the role of natural host immunity in combatting parasitic infection is unclear, so further research on natural host immunity against parasites will provide a theoretical basis for the prevention and treatment of related parasitic diseases. Extracellular traps (ETs) are an important natural mechanism of immunity involving resistance to pathogens. When immune cells such as neutrophils and macrophages are stimulated by external pathogens, they release a fibrous network structure, consisting mainly of DNA and protein, that can capture and kill a variety of extracellular pathogenic microorganisms. In this review, we discuss the relevant recently reported data on ET formation induced by protozoan parasite infection, including the molecular mechanisms involved, and discuss the role of ETs in the occurrence and development of parasitic diseases.